Impact of co‐morbidities on health‐related quality of life 10 years after surgical treatment of oesophageal cancer. Issue 4 (29th May 2020) - Klevebro, F.; Johar, A.; Lagergren, P.
Abstract : Background: Oesophagectomy for cancer is associated with long‐term decreased health‐related quality of life (HRQoL). The aim of this study was to evaluate the effect of co‐morbidities on HRQoL among survivors of oesophageal or gastro‐oesophageal junctional cancers after 10 years or more. Methods: The study included a prospectively collected, population‐based cohort, comprising all patients who had surgery for oesophageal or gastro‐oesophageal junctional cancer in Sweden in 2001–2005 with follow‐up until 31 December 2016. All data regarding patient and tumour characteristics, treatment details and HRQoL were collected using a prospectively created database. Multivariable ANCOVA regression models, adjusting for age, sex, tumour histology, stage and surgical technique, were used to calculate adjusted mean scores with 95 per cent confidence intervals for all HRQoL outcomes. Results: A total of 92 survivors (88·5 per cent) responded to the questionnaires. Patients were stratified in two groups according to whether they reported a low or high impact of co‐morbidities on general health. Patients in the high‐impact group had clinically significantly decreased HRQoL and an increased level of symptoms, but differences between these two groups were not statistically significant. Conclusion: Co‐morbidities with high impact on general health still contribute to impaired HRQoL 10 years after oesophagectomy for cancer. Abstract : This study investigated the impact of co‐morbidities on health‐related quality of life during long‐term follow‐up after oesophagectomy. The results showed that the substantial impact of co‐morbidities on reported general health might be associated with symptoms and health‐related quality of life 10 years after oesophageal cancer treatment. Co‐morbidities affect long‐term QOL. Abstract : Antecedentes: La esofaguectomía por cáncer se asocia con un descenso de la calidad de vida relacionada con la salud ( health‐related quality of life, HRQoL) a largo plazo. El objetivo de este estudio fue evaluar el efecto de las comorbilidades sobre la HRQOL entre pacientes supervivientes de cánceres de esófago o de la unión gastroesofágicas después de 10 años o más. Métodos: Este estudio incluye una cohorte de base poblacional recogida de forma prospectiva que incluía todos los pacientes operados de cáncer de esófago o de la unión gastroesofágica en Suecia en 2001‐2005 con seguimiento hasta el 31 de diciembre de 2016. Todos los datos relacionados con las características de los pacientes y del tumor, detalles del tratamiento y HRQoL se recogieron en una base de datos prospectiva. Se utilizaron modelos de regresión multivariable ANCOVA, ajustados por edad, sexo, histología del tumor, estadio, y técnica quirúrgica, para calcular las puntuaciones medias ajustadas con los i.c. del 95% para todas las variables de la HRQoL. Resultados: Un total de 92 (88%) supervivientes respondieron a los cuestionarios. En función del impacto de las comorbilidades en la salud en general, se clasificaron a los pacientes en los grupos de bajo versus alto impacto. Los resultados muestran que los pacientes en el grupo de alto impacto presentaban un descenso clínicamente significativo de la HRQoL y un aumento en el nivel de síntomas, pero las diferencias entre estos dos grupos no fueron estadísticamente significativas. Conclusión: A los 10 años de la esofaguectomía por cáncer, las comorbilidades con un alto impacto sobre la salud general siguen contribuyendo en el deterioro de la HRQoL.